Study on Development of Phage Synthesising System by Minimising Approach - Hideo Ogimura (Emerging Trends in Disease and Health Research Vol. 3, 2022)
The synthesis of life has been the vision of mankind. I consider the creation of life to the almost same as understanding life. I also consider the concept of life is quasi-equal to viruses. Further the reason I selected the minimizing approach is that understanding of "life" to be the division of the real chaotic world into smaller ones. I successfully established a minimum phage synthesizing system. This system is under non-equillibrium state. I also precisely identified tRNAs as the factors related to the synthesis of plaque-forming units. In this study, I showed that it is possible to create life from very simple organic materials. This system may be applicable to other pathogenic viruses, and it could be used to synthesize novel drugs.